Faktor-faktor yang Mempengarui Perilaku Seksual Anak Jalanan Perempuan di Kabupaten Banyumas - Surono, Dwi Cahyaningtiyas; Riani, Evicenna Naftuchah; Pangesti, Wilis Dwi; Mu'minah, Ikhwah (LPPM Hang Tuah Pekanbaru, 2024)
Sexual behavior is an attitude driven by sexual desire, both to the opposite or the same sex. In Indonesia, 1.2% of adolescents fall into free sex or sex before marriage. The most significant percentage was male adolescents or 1.9%. The same condition also occurred in the province of Central Java, with a percentage more significant than the national or 1.3% who had sexual intercourse, and the majority were male adolescents 1.1%. The study aimed to explore the factors affecting sexual behavior in female street children in Banyumas Regency. This qualitative study used a case study design that selected informants from street children in Banyumas Regency. In-depth interviews and observations were conducted in this research. The findings prove that the factors affecting the sexual behavior of street children in Banyumas Regency were knowledge, religious norms, socio-economics, the effect of friends, information media, and opportunities. In addition, other factors that affected the sexual behavior of female street children were parents, environment with friends, libido, and education. One factor did not affect sexual behavior, namely the consumption of alcohol and illegal drugs. So knowledge, religious norms, socio-economics, friends, media information, opportunities, parents, environment with friends, libido, and education affected sexual behavior.